Implementasi Teknologi Augmented Reality dalam Pembelajaran Interaktif - Indahsari, Leoni; Sumirat, Sumirat (CV. Lenggogeni Data Publishing, 2023)
Interactive learning has become a primary focus in the development of modern education. With the rapid advancement of technology, Augmented Reality (AR) has emerged as an exciting and innovative tool in enhancing interactive learning. This article aims to elucidate the implementation of Augmented Reality technology in interactive learning and its benefits for students. We will discuss the fundamental concept of Augmented Reality, its usage in the educational context, and provide examples of its application in the classroom. The article will also explore the benefits and challenges associated with the use of Augmented Reality technology in interactive learning. Abstrak Pembelajaran interaktif telah menjadi fokus utama dalam pengembangan pendidikan modern. Dengan perkembangan teknologi yang pesat, Augmented Reality (AR) telah muncul sebagai alat yang menarik dan inovatif dalam membantu pembelajaran interaktif. Artikel ini bertujuan untuk menjelaskan implementasi teknologi Augmented Reality dalam pembelajaran interaktif serta manfaatnya bagi siswa. Kami akan membahas konsep dasar Augmented Reality, penggunaannya dalam konteks pendidikan, dan beberapa contoh penerapannya dalam ruang kelas. Artikel ini juga akan membahas manfaat dan tantangan yang terkait dengan penggunaan teknologi Augmented Reality dalam pembelajaran interaktif. Kata kunci: Interactive learning, Augmented Reality (AR), Educational technology